Chemical-Physical Characteristics of Edible Film Incorporated Bali Cattle Hide Gelatin and Encapsulated Gaharu Leaf Extract - Miwada Sumirtha; Sumadi Ketut; Wrasiati Wrasiati; Sutama Sutama; Tirta Ariana; Bulkaini Bulkaini (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The objectives of this study were to analyze the potential of incorporating bali cattle hide gelatin and gaharu leaf extract encapsulated as an edible film with antioxidant potential. The research method was using Completely Randomized Design, ie concentration of gaharu leaf extract encapsulated (G0 = 0%, G1 = 5%, G2 = 10%, G3 = 15% and G4 = 20%). The results showed that the characteristics of edible films were significantly different (P <0.05), such as moisture content (7.37%) in G4; protein (86.25%) in G0, phenol (10.84 mg / 100 g GAE) in G4 and antioxidant (150.36 mg / L. GAEAC) in G4, and the effect was not significant on ash content of the film. It film thickness, tensile strength, elongation, and water vapor transmission rate of edible film were significant (P <0.05) influence with results for 0.04 mm (G0); 1.64 Mpa (G0); 54.86% (G1) and 11.20 g.mm/m2.day in G4, respectively. The conclusion of the research is edible film of incorporation of balicattle skin bali gelatin and gaharu leaf extract encapsulated with 20% concentration yielding functional characteristics (potency antioxidant) with the highest value. Indicators of chemical characteristics include moisture content (7.37%); ash content (0.49%); protein content (71,98%); phenol (10.84 mg / 100 g GAE) and antioxidant (150.36 mg / L GAEAC). While physical indicators include film thickness (0.02 mm); tensile strength (1.54 MPa); elongation (71.48%) and water vapor transmission rate (11.20 g.mm/m2.day).